Co-existence of Secular Taxation and Syariah Compliant Practices : A Contemporary Application - Ern Chen, Loo; Anuar, Muhammad; Mohd Waliuddin, Mohd Razali (Human Resource Management Academic Research Society, 2023)
In Malaysia, the administration of zakat institutions comes under the respective individual State jurisdictions while that of secular taxes comes under the Federal Government. Unlike Syariah-compliant practices, certain aspects of secular tax practices are not Syariah-compliant. Despite these two fundamental diverse features, secular taxation and Syariah-compliant practices have been able to co-exist within the Malaysian fiscal system, made possible by the provisions in Federal secular tax codes and fiscal policies that accommodate Syariah-compliant transactions and arrangements, by explicitly excluding certain Syariah-compliant transactions and arrangements from falling under the ambit of the secular tax laws. In addition, parallel tax treatments based on the principles of tax neutrality and specific tax incentives for Syariah-compliant transactions and arrangements are provided.